PENGARUH LABEL HALAL, PERSEPSI HARGA, DAN PENDAPATAN TERHADAP KONSUMSI PRODUK OBAT BATUK (Studi Kasus di Wilayah Kota Malang) - Trihatmojo, Gandhi Raka; Muljaningsih, Sri (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2022)
This research is aimed to discover whether or not there is an effect of Halal labels, price perception as well as income levels on cough medicine consumption. The subject of this research are the 123 residents of Malang city, East Java using quantitative methodology. According to the results of this research, there is a positive relationship in between the effect of Halal label, price perception, plus income levels and cough medicine consumption. Of all independent variables, the one that gives the most significant effect is the presence of Halal labels. With that being said, this research suggests that the government or Islamic religious authorities accelerate Halal certification on cough medicines, as well as medicine manufacturers to increase affordable yet high quality cough medicine productions so that the public can have equal access to the medicine’s benefits Kata Kunci: Halal, Obat Batuk, Harga, Penghasilan